Localization of the site of fixation of the inducer, penicillin, in Bacillus cereus - Duerksen, J.D. (Biochimica et biophysica acta, 1964)
1. 1. The rupture of [ 35S]penicillin treated Bacillus cereus in a pressure cell solubilized the majority of the specifically bound radioactivity. Upon conversion of [ 35S]penicillin treated cells to protoplasts approx. 95% of the label was found in the lysozyme digest supernatant and not associated with the protoplasts. In either case the bound label was still associated with a large molecular weight component. 2. 2. The bound label was not found to be associated with the ribosomes, messenger RNA, purified cell wall, or purified cytoplasmic membrane. Localization of the bound penicillin to a component closely associated with the cytoplasmic membrane-cell wall area is strengthened by the finding that a combination of lipase (EC 3.1.1.3) and trypsin (EC 3.4.4.4) caused a major portion of the bound radioactivity to become dialyzable. This latter result indicates that the cell structure to which penicillin binds is a lipoprotein. 3. 3. The release of the penicillin-receptor complex during protoplast formation explains the results that protoplasts do not fix [ 35S]penicillin similar to whole cells and that protoplasts cannot be induced to a higher rate of penicillinase (penicillin amidohydrolase, EC 3.5.2.6) formation by addition of penicillin. A 30 to 60 min induction of the inducible strain with penicillin is required for the subsequently formed protoplasts to synthesize penicillinase at comparable rates to induced whole cells.